2016
DOI: 10.21608/ejhc.2016.54588
|View full text |Cite
|
Sign up to set email alerts
|

Quality of work life as perceived by staff nurses and its relation to their turnover intention at critical care units

Abstract: A high quality of work life (QWL) is essential and critical for hospitals to attract new nurses and retain qualified and motivated workforce. Consequently, hospitals are seeking ways to address the issues of recruitment and retention by achieving a high QWL. The aim of this study was to assess quality of work life as perceived by staff nurses and its relation to their turnover intention at critical care units. A descriptive correlational design was utilized. The study was conducted at 5 critical care units in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The characteristics of each study are detailed in Table 2. Eighteen studies 15,19,29‐44 involving 23 140 ICU nurses were included in the study. All included studies were published between 2007 and 2020.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of each study are detailed in Table 2. Eighteen studies 15,19,29‐44 involving 23 140 ICU nurses were included in the study. All included studies were published between 2007 and 2020.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of each study are detailed in Table 2. Eighteen studies 15,19,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] The mean study quality score across the included studies was 5.2.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Also, Abdelhakam et al, (2015) who assessed quality of work as perceived by staff nurses and its relation to their turnover intension at critical care units, reported that the majority of the nurses were not able to balance work with their family needs.…”
Section: Discussionmentioning
confidence: 99%
“…Personal Table (1), reveals that, 85% of the respondents were female, 58.8% held associate degree in nursing, 78.8% of the study sample were had less than 10 years' experience in nursing, while 56.3% of them were had less than 10 years' experience in current place. 1): revealed that, 88% of the studied sample perceived work design as average, followed by 79% of the studied sample perceived total QNWL Scores as average, then 74% of them perceived work world as average and 52% of them perceived work life as average, while 30% of the studied sample perceived work context as average level.…”
Section: Table (1): Distribution Of the Studied Nurses ' Personal Data (N= 80)mentioning
confidence: 97%
See 1 more Smart Citation